The Influence of Stakeholder Participation and Institutional Coordination on the Effectiveness of Adaptive Coastal Governance - Fira Landoni; Indri Oktaviani; Susianti Susianti (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study aims to examine the influence of stakeholder participation and institutional coordination on the effectiveness of adaptive coastal governance in Bulukumba. Subjects and Methods: A quantitative explanatory design was employed using a cross-sectional survey of key stakeholders, including government agencies, community groups, and NGOs. Data were collected through structured questionnaires and analyzed using Pearson correlation and multiple linear regression to assess relationships and predictive effects. Results: The findings reveal that both stakeholder participation and institutional coordination have significant positive effects on governance effectiveness, with participation emerging as the stronger predictor. The model demonstrates substantial explanatory power, indicating that governance outcomes are shaped by the interaction of relational and institutional factors. Participation enhances inclusiveness, legitimacy, and adaptive capacity, while coordination ensures policy coherence and implementation consistency. Conclusions: Effective adaptive coastal governance requires the integration of meaningful stakeholder engagement and strong institutional coordination to achieve resilient, responsive, and sustainable governance systems.